دور الوسطية في وحدة الأمة الإسلامية - Mesbahul Hoque; Kauthar Abd Kadir; Yuslina Mohamed; Muneer Ali Abdul Rab (USIM Press, 2024)
Moderation is a means for the unity, safetyand security of this Ummah from division and fragmentation, as the moderate idea is what guarantees the unity of the conflicting parties and their gathering on one level. Moderation saves also the Ummah from falling into the clutches of infidelity, blasphemy and misguidance. Any deviation from moderation will lead the person to excessiveness or negligence, both of which are among the causes of the Ummah’s disunity and dispersal, and the loss of its security and safety. Therefore, Allah S. W.T describe the moderation as a characteristic of this Ummah, as Allah S.W.T said: “And thus, we have made you a middle nation so thatyou may be witnesses over people and that the Messenger will be witnesses for you” (Al-Baqarah:143). This study comes to shed light on moderation and its impact on the unity and integrity of the Ummah by using some appropriate approaches to it, such as the descriptive, inductive and analytical method. One of the most important results of the study is that moderation has a broad concept in Islam, and it is the criterion of the nation’s unity and its safety ship from destruction